Maternal preconception BMI and gestational weight gain are associated with weight retention and maternal and child body fat at 6–7 years postpartum in the PRECONCEPT cohort - Young, Melissa F.; Nguyen, Phuong Hong; Tran, Lan Mai; Khuong, Long Quynh; Hendrix, Sara; Martorell, Reynaldo; Ramakrishnan, Usha (Frontiers Media, 2023)
Background: There is limited evidence from prospective cohorts in low-resource settings on the long-term impact of pre-pregnancy body mass index (PPBMI) and gestational weight gain (GWG) on postpartum weight retention (PPWR) and maternal and child body composition. Objectives: We examined the associations between PPBMI and timing of GWG on PPWR at 1, 2, and 6–7 years and maternal and child percent body fat at 6–7 years. Methods: We used data from the PRECONCEPT study (NCT01665378) that included prospectively collected data on 864 mother–child pairs from preconception through 6–7years postpartum. The key outcomes were PPWR at 1, 2, and 6–7years, and maternal and child percent body fat at 6–7years that was measured using bioelectric impedance. Maternal conditional GWG (CGWG) was defined as window-specific weight gains (< 20wk, 21-29wk, and ≥ 30wk), uncorrelated with PPBMI and all prior body weights. PPBMI and CGWG were calculated as standardized z-scores to allow for relative comparisons of a 1 standard deviation (SD) increase in weight gain for each window. We used multivariable linear regressions to examine the associations, adjusting for baseline demographic characteristics, intervention, breastfeeding practices, diet and physical activity. Results: Mean (SD) PPBMI and GWG were 19.7 (2.1) kg/m2 and 10.2 (4.0) kg, respectively. Average PPWR at 1, 2, and 6–7years was 1.1, 1.5 and 4.3kg, respectively. A one SD increase in PPBMI was associated with a decrease in PPWR at 1 year (β [95% CI]: −0.21 [−0.37, −0.04]) and 2 years (−0.20 [−0.39, −0.01]); while a one SD in total CGWG was associated with an increase in PPWR at 1 year (1.01 [0.85,1.18]), 2 years (0.95 [0.76, 1.15]) and 6–7 years (1.05 [0.76, 1.34]). Early CGWG (< 20weeks) had the greatest association with PPWR at each time point as well as with maternal (0.67 [0.07, 0.87]) and child (0.42 [0.15, 0.69]) percent body fat at 6–7years. Conclusion: Maternal nutrition before and during pregnancy may have longterm implications for PPWR and body composition. Interventions should consider targeting women preconception and early in pregnancy to optimize maternal and child health outcomes.